Swimming exercise attenuates mechanical hypersensitivity and mitigates peripheral nerve degeneration in rats with painful diabetic neuropathy (PDN) - Zhu, G-C; Chen, Y-W; Tsai, K-L; Wang, J-J; Hung, C-H; Schmid, AB (Elsevier, 2023)
Background: This study aimed to assess the effectiveness of swimming exercise in alleviating mechanical hypersensitivity and peripheral nerve degeneration associated with a pre-clinical model of painful diabetic neuropathy (PDN). Methods: This study is a pre-clinical study conducted using the streptozocin (STZ)-induced PDN rat model. Rats were randomly allocated to three groups: a vehicle group of non-diabetic rats (Vehicle, n = 9), a group of rats with PDN (PDN, n = 8), and a group of rats with PDN that performed a swimming exercise program (PDN-SW, n = 10). The swimming exercise program included daily 30-minute swimming exercise, 5 days per week for 4 weeks. Von Frey testing was used to monitor hindpaw mechanical sensitivity over 4 weeks. Assessment of cutaneous peripheral nerve fiber integrity was performed after the 4-week study period via immunohistochemistry for protein gene product 9.5-positive (PGP9.5+) intra-epidermal nerve fiber density (IENFD) in hind-paw skin biopsies by a blinded investigator. Results: The results showed that swimming exercise mitigated but did not fully reverse mechanical hypersensitivity in rats with PDN. Immunohistochemical testing revealed that the rats in the PDN-SW group retained higher PGP9.5+ IENFD compared to the PDN group but did not reach normal levels of the Vehicle group. Conclusions: The results of this study indicate that swimming exercise can mitigate mechanical hypersensitivity and degeneration of peripheral nerve fibers in rats with experimental PDN.